EFFECT OF ACHIEVEMENT MOTIVATION ON SATISFACTION AND ACADEMIC PERFORMANCE OF STUDENTS - Nasira Parveen; Dr. Muhammad Naveed Jabbar; Roheela Begum (International Journal of Contemporary Issues in Social Sciences, 2024)
The academic performance of the students is a foremost concern for the development of the educational institutions. This objective can be achieved through the achievement of motivation and satisfaction of the students. The aim of this research was to examine the effectiveness of achievement motivation on satisfaction and academic performance of students. The study population was students, and 296 respondents were selected from public secondary schools from Bahawalnagar by applying convenience sampling technique. A self-administered instrument was developed to collect the data by administering survey method. SPSS was computed to analyze the research objectives. The findings indicated that achievement motivation had been seen significantly correlated with achievement motivation and academic performance. Whereas there was more positive relationship of achievement motivation with academic performance than students’ satisfaction. Furthermore, there was a more positive effect of achievement motivation on academic performance as compared to students’ satisfaction. This research is beneficial for the development of the learning process by adopting various strategies